Rearranging Differential Inclusion through Civic Solidarity: Loose Coupling in Mentorship for “Unaccompanied Minors” - Eberhard Raithelhuber (Social Inclusion, 2019)
This article looks into a community-based mentoring programme for unaccompanied refugee minors (URMs), launched in 2015 at the peak of refugee movement in Austria. Leaning on a long-term ethnographic study, it sheds light on dynamic developments in refugee support through civic solidarity. The article proposes that examining the programme from the point of view of dialectic processes of organizing provides a better standpoint for asking what was produced on the programme and what influences those outcomes have had on more contentious political dimensions. Following this, the focus is concentrated on “loose coupling” within a pilot youth mentoring scheme. This reveals how inbuilt ambiguities were given structure, how rationality and indetermination were interdependently organized and how the uncertain was ascertained through mentor training and matching. Thus, unequal but personal relationships were brought about and stabilized. The particular institutionalization of “godparenthoods for URMs” offered possible ways of integrating various elements of a support system in a way which could provide better support than other relationships amongst strangers. I argue that these specific forms of loose coupling opened up a corridor in which aspects relating to the differential inclusion of young refugees were (re-)arranged through adults volunteering, but with mixed results.